Pengaruh Akuntabilitas, Kualitas Pelayanan, Kepercayaan Muzakki terhadap Loyalitas Muzakki - Jumriani Jumriani (Journal of Islamic Management, 2021)
Effect of accountability, quality of service, trust Muzakki on loyalty to Muzakki. This research aims to discuss the influence of accountability, quality of service, trust Muzakki on Muzakki loyalty to the institution Muzakki Management Institute Infaq (LMI) Surabaya. The research method is using a quantitative approach. The Unit of analysis in research is to use respondents Muzakki for 100 Muzakki in the area of Surabaya, with the research instrument using the questionnaire in the area of Surabaya, and the method of data analysis using multiple linear regression. The results showed that the simultaneous influence was positive and significant and partiality that accounting was influential towards Muzakki loyalty, the quality of service was influential on Muzakki loyalty, and Muzakki's belief had an effect on Muzakki loyalty